The course of the posterior interosseous nerve in relation to the proximal radius: Is there a reliable landmark?. Issue 4 (April 2015) - Hackl, M.; Wegmann, K.; Lappen, S.; Helf, C.; Burkhart, K.J.; Müller, L.P.
Abstract: Purpose: The posterior interosseous nerve (PIN) is closely related to the proximal radius, and it is at risk when approaching the proximal forearm from the ventral and lateral side. This anatomic study analyzes the location of the PIN in relation to the proximal radius depending on forearm rotation by means of a novel investigation design. The purpose of this study is to define landmarks to locate the PIN intraoperatively in order to avoid neurological complications. Methods: We dissected six upper extremities of fresh-frozen cadaveric specimens. The mean donor age at the time of death was 81.2 years. The PIN was dissected and marked on its course along the proximal forearm with a 0.3-mm flexible radiopaque thread. Three-dimensional (3D) X-ray scans were performed, and the location of the nerve was analyzed in neutral rotation, supination, and pronation. Results: In the coronal view, the PIN crosses the radial neck/shaft at a mean of 33.4 (±5.9) mm below the radial head surface (RHS) in pronation and 16.9 (±5.0) mm in supination. It crosses 4.9 (±2.2) mm distal of the most prominent point of the radial tuberosity (RT) in pronation and 9.6 (±5.2) mm proximal in supination. In the sagittal view, the PIN crosses the proximal radius 61.8 (±2.9) mm below the RHS in pronation and 41.1 (±3.6) mm in supination. The nerve crosses 29.2 (±6.2) mm distal of the RT in pronation and 11.0 (±2.8) mm in supination. Conclusion: With this novel design, the RT could be defined as a useful landmark for intraoperative orientation. On a ventral approach, the PIN courses 10 mm proximal of it in supination and 5 mm distal of it in pronation. Laterally, pronation increases the distance of the PIN to the RT to approximately 3 cm.